Not so common pottery: the microcosm of kitchen wares from the area E of Nora (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
Among all the archaeological indicators that can be used to investigate ancient societies, the cooking wares provides relevant information on eating habits, habits that tend to be fixed in time and shared by social groups. It is a microcosm of information that needs to be investigated in a longer period and in a diachronic way, by studying technical and typological features’ changes. Investigating the evolution of cooking sets can be fundamental to understand the limits of spheres of influence between contiguous cultural groups and areas. Nora, thanks to its position in the middle of a range of cultural influences, could be a very good observatory of these cultural phenomena.
Keywords: cooking wares; cooking habits; cooking sets; cultural influences